Awkwardly ever after - Bates, Marni. (Kensington Books, 2014)
"Melanie Morris knows she shouldn't keep flirting with her best friend's brother, Dylan Wellesley, even though the last thing she feels is "sisterly" around the cute soon-to-be freshman. But attending prom with somebody else might mean losing him for good. Isobel Peters accepts the fact that she's a huge geek, but she never expected renowned player, Spencer King, would want to get his hands on ... her reputation. What begins as a bargain could turn into something real--or a Notable disaster! Corey O'Neal is dating the boy of his dreams, rockstar Timothy Goff. But it isn't easy to trade in anonymity for instant celebrity status, especially now that swarms of protesters want them both banned from prom. Dating Prince Charming in real life is a whole lot harder than it sounds in fairytales. Happily ever after? Try awkwardly ever after!"--Back cover.